ANALISIS PRAKTIK KESIAPSIAGAAN PETUGAS KEAMANAN TERHADAP PENANGGULANGAN BAHAYA KEBAKARAN DI MALL X SEMARANG - Yohana Efelin; Daru Lestantyo; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2018)
Preparedness is effort to allow people to overcome disaster hazard through the systematic emergency response and organization. Mall is a public place that is located near the city buildings and have a place to shop, gather, or a place for recreation. Mall have quite a variety of fire characteristics, it classified into sixth level of fire, variation of occupant, and variation of hazards. The purpose of this research was to analyze factors that related to preparedness practices. The design of this study was analytic-quantitative research with cross-sectional approach. Population of this research were 59 security officers of X Mall Semarang. Sampling of this research were 59 security officers (total samping). Questionnaire and observation checklist were used as the instruments of this research. The observation sheet was used to check the suitability of existing fire prevention facilities with the prevailing standards in Indonesia. Statistical analysis used was chi-square test. The result of the research showed that there was a relation between knowledge (p=0,027), attitude (p=0,025), fire protection facilities (p=0,001), fire rescue training (p=0,000) with preparedness practices, while there was no relation between supervision of HSE officer (p=0,731) with preparedness practices. Researchers suggest company to provide socialization of fire and safety about shopping center to security and complete the fire protection facility.